Школа академіка Романа Кучера: досягнення в науці та практиці (до 100-річчя академіка НАН України Р. В. Кучера) - Опейда, Й.О.; Раєнко, Г.Ф.; Попов, А.Ф. (Вісник НАН України, 2025)
Статтю присвячено пам’яті видатного українського вченого в галузі фізичної хімії, кінетики та каталізу, талановитого організатора науки, лауреата Державної премії України в галузі науки і техніки (1993), лауреата премії імені Л.В. Писаржевського НАН України (1969), директора Інституту геології і геохімії горючих копалин НАН України (1982—1986), керівника Відділення фізико-хімії і технології горючих копалин Інституту фізичної хімії ім. Л.В. Писаржевського НАН України (1986—1991), доктора хімічних наук (1964), професора (1966), дійсного члена НТШ (1992), академіка НАН України (1973) Романа Володимировича Кучера. March 12 marks a century since the birth of Roman Volodymyrovych Kucher, an outstanding Ukrainian scientist in the field of physical chemistry, kinetics and catalysis, a talented organizer of science, laureate of the State Prize of Ukraine in the field of science and technology (1993), laureate of the L.V. Pisarzhevsky Prize of the NAS of Ukraine (1969), director of the Institute of Geology and Geochemistry of Combustible Minerals of the NAS of Ukraine (1982—1986), head of the Department of Physical Chemistry and Technology of Combustible Minerals of the L. Pisarzhevsky Institute of Physical Chemistry of the NAS of Ukraine (1986—1991), Doctor of Chemical Sciences (1964), Professor (1965), full member of the Shevchenko Scientific Society (1992), Academician of the NAS of Ukraine (1973).